Interplay-sports : The Ultimate Video Analysis and Scouting Software (2012)
Interplay-sports is the next step in modern video analysis software. Interplay-sports Pro is the ultimate video analysis software for national teams and clubs. Interplay-sports MiniPro is the perfect tool for developing your young players. A leading tool for Match analysis live or post-production allow you to you to analyse every aspect of your games and improve your players performance. The video analysis can easily be done during the game when connected to a camera, or in a post-production process after the game from the camera, from DVD's or uploaded video files. Interplay-sports has an range of products that meet needs of the most advanced analyzes to the simple video analyzes for youth team. The ball lab in University of sports Norway powered with Interplay-sports Pro for complex video analysis and tracking statistics.